Development of Assessment Instruments with a Contextual Approach to Determine the Profile of Conservation Education and Learning Independence on Biodiversity - Nurandari*, Bellamerna Dwi Nawangsih; Paidi, Paidi; Subiantoro, Agung Wijaya; Pratama, Anggi Tias; Abd Wahid, Nurul Bahiyah (Universitas Syiah Kuala, 2024)
Conservation education is one of the noble values that must be preserved and students can maintain the sustainability of biodiversity around them. This study aimed to develop an assessment instrument to determine the profile of conservation education and learning independence on biodiversity. This type of research is R D with a 4-D model. The population of the study is all students of grade 10 of State Senior High School 1 Godean and the samples used are grade 10D and 10F. The data collection technique used a five-question essay instrument sheet to determine conservation education and a Guttman scale questionnaire instrument to determine learning independence. The analysis technique used descriptive quantitative and qualitative. The results of this study were that the instrument was said to be good with revisions according to the construct validator. The validity of the question items showed that the essay questions were said to be valid, reliable, had a discriminatory power between good enough, and the difficulty level ranged from easy to moderate according to the empirical validator. The value of students' conservation education fell into the good category with a complete value achievement of 73%. Students' learning independence is also classified as very high, because all indicators are dominated by very high indicators. These results indicate that the profile of conservation education and learning independence of students at State Senior High School 1 Godean is classified as good and very high